2021
DOI: 10.1186/s12863-020-00957-w
|View full text |Cite
|
Sign up to set email alerts
|

Pineal gland transcriptomic profiling reveals the differential regulation of lncRNA and mRNA related to prolificacy in STH sheep with two FecB genotypes

Abstract: Background Long noncoding RNA (lncRNA) has been identified as important regulator in hypothalamic-pituitary-ovarian axis associated with sheep prolificacy. However, little is known of their expression pattern and potential roles in the pineal gland of sheep. Herein, RNA-Seq was used to detect transcriptome expression pattern in pineal gland between follicular phase (FP) and luteal phase (LP) in FecBBB (MM) and FecB++ (ww) STH sheep, respectively, and differentially expressed (DE) lncRNAs and mR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Ovulation rate (the number of corpus luteum) was detected by the laparoscopy procedure after 7 days from the CIDR removal (luteal phase), which is a key index determining sheep prolificacy. Then, the estrus synchronization mentioned above was performed again after 45 h from the CIDR removal, and ovaries with follicle diameter ≥ 3.5 mm were obtained (follicular phase) ( 12 , 29 ). The 12 ewes were divided into four groups, including polytocous ewes in the follicular phase (PF, n = 3), polytocous ewes in the luteal phase (PL, n = 3), monotocous ewes in the follicular phase (MF, n = 3), and monotocous ewes in the luteal phase (ML, n = 3).…”
Section: Methodsmentioning
confidence: 99%
“…Ovulation rate (the number of corpus luteum) was detected by the laparoscopy procedure after 7 days from the CIDR removal (luteal phase), which is a key index determining sheep prolificacy. Then, the estrus synchronization mentioned above was performed again after 45 h from the CIDR removal, and ovaries with follicle diameter ≥ 3.5 mm were obtained (follicular phase) ( 12 , 29 ). The 12 ewes were divided into four groups, including polytocous ewes in the follicular phase (PF, n = 3), polytocous ewes in the luteal phase (PL, n = 3), monotocous ewes in the follicular phase (MF, n = 3), and monotocous ewes in the luteal phase (ML, n = 3).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Danila Cuomo et al [ 19 ] screened 636 lncRNAs that were mainly enriched with PI3K-Akt and TGF-β signaling pathways, which were closely related to the regulation of follicle development and steroid-hormone biosynthesis. Chunyan Li et al [ 20 ] identified six lncRNAs in the sheep pineal gland between the follicular phase and luteal phase, which could participate in hormone activities to affect sheep reproductive performance via regulation of its target genes. Yang et al [ 9 ] identified some lncRNAs, and their target genes were enriched with male-gonad-development signaling pathways.…”
Section: Introductionmentioning
confidence: 99%